THE INFLUENCE OF LABOR, SOCIAL MEDIA, AND PEOPLE’S BUSINESS CREDIT ON THE INCOME OF MICRO CULINARY ENTERPRISES IN DENPASAR CITY - I Wayan Arsa Aditya; A.A. Ketut Ayuningsasi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Culinary micro-enterprises in Denpasar City are growing rapidly and becoming a leading sector in supporting regional economic growth. However, high levels of competition, limited skilled labor, low utilization of social media, and limited access to capital are major challenges in increasing business revenue. This study aims to analyze the influence of labor, social media, and people's business credit on the revenue of culinary micro-enterprises in Denpasar City, both simultaneously and partially. This study uses a quantitative approach with an associative research type. A sample of 100 respondents was determined through proportional stratified random sampling method, with respondents being drawn by accidental sampling in four sub-districts in Denpasar City. Primary data collection was conducted through field observations and questionnaires, while secondary data were obtained from official agencies such as the Denpasar City Cooperatives and MSMEs Office and the Central Statistics Agency. The data analysis technique used was multiple linear regression with the classical assumption test, the F test, and the t test to examine the influence of independent variables simultaneously and partially on business revenue. The results show that simultaneously, labor, social media, and people's business credit influence the income of culinary micro-enterprises in Denpasar City. Partially, labor has a positive and significant effect on the income of culinary micro-enterprises in Denpasar City. Furthermore, the income of culinary micro-enterprises in Denpasar City that use social media is higher than those that do not use social media, and the income of culinary micro-enterprises in Denpasar City that use people's business credit loans is higher than those that do not use people's business credit loans. It is recommended that culinary micro-enterprises optimize working hours and workforce productivity, utilize social media as a digital marketing tool, and access people's business credit programs optimally to increase competitiveness and business income.